Securing Video on Demand Content with SGX: A Decryption Performance Evaluation in Client-Side - Costa, Ricardo de S.; Pigatto, Daniel F.; Fonseca, Keiko V. O.; Rosa, Marcelo de O. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2018: Anais do XVIII Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2018.4248, 2018)
Video on Demand (VoD) is presently a bandwidth demanding application of IPTV networks but also a source of revenue for content providers, broadcasters and infrastructure providers. Customers can select TV content like movies and shows from a wide digital media library, and are no longer tied to a fixed schedule. The programming content is digitally compressed, stored and kept at VoD storage drives and flows from them to residential set-top boxes (STB) according to the user demand. However VoD service should set the streaming of a chosen content only to authorized clients, that is, the system should secure the data transfer and storage in order to prevent copyright infringements or unfair business competition with content illegally acquired. This paper proposes the adoption of SGX technology as a solution for a secure VoD service focusing in client-side (embedded devices) and evaluating its decryption performance. We show that video chunks normally transfered between media servers and real STBs can be decrypted in approximately 150μs, on average, which is enough for using this technology in STBs.